Analysis of Personal Data Vulnerabilities in Legal Online Loan Transactions - Afronal; Puspita, Maria; Aminanto, Muhammad Erza (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
This research examines the vulnerability of personal data in online loan transactions in Indonesia. Advances in financial technology have created a rapidly growing fintech industry, which includes online lending services. However, the use of personal data in these transactions carries serious potential risks related to the vulnerability of personal data. In this research, the author uses a descriptive qualitative approach by combining interviews and secondary data analysis from literature related to personal data protection in Indonesia. The research results show that personal data used in online loan transactions has a high attraction for irresponsible online loan managers. The vulnerability of personal data in online loan transactions is reflected in various threats, including cyber-attacks that can cause serious financial and reputational losses for individuals involved in these transactions. This will ultimately cause social and psychological costs for the victim. Stricter measures in protecting personal data and strengthening security policies in online loan applications are necessary to reduce the risk of these vulnerabilities. This research also identifies legal provisions governing personal data protection and underscores the need for awareness of privacy rights and data security in the fintech industry.